Kuladevata of the family - Mumbai Archive Project Team (Jio Institute, 2024)
The kuladevata is the ancestral tutelary deity of the family kul (lineage), worshipped for the protection of family members. Khandoba is the kuladevata of the Nakhva family, with the main temple located in Jejuri, Pune district, Maharashtra.